Downregulation of CPSF6 leads to global mRNA 3' UTR shortening and enhanced antiviral immune responses. - Yong Ge; Jingrong Huang; Rong Chen; Yonggui Fu; Tao Ling; Xin Ou; Xiaohui Rong; Youxiang Cheng; Yi Lin; Fengyi Zhou; Chuanjian Lu; Shaochun Yuan; et al. (PLoS Pathogens, 2024)
Alternative polyadenylation (APA) is a widespread mechanism of gene regulation that generates mRNA isoforms with alternative 3' untranslated regions (3' UTRs). Our previous study has revealed the global 3' UTR shortening of host mRNAs through APA upon viral infection. However, how the dynamic changes in the APA landscape occur upon viral infection remains largely unknown. Here we further found that, the reduced protein abundance of CPSF6, one of the core 3' processing factors, promotes the usage of proximal poly(A) sites (pPASs) of many immune related genes in macrophages and fibroblasts upon viral infection. Shortening of the 3' UTR of these transcripts may improve their mRNA stability and translation efficiency, leading to the promotion of type I IFN (IFN-I) signalling-based antiviral immune responses. In addition, dysregulated expression of CPSF6 is also observed in many immune related physiological and pathological conditions, especially in various infections and cancers. Thus, the global APA dynamics of immune genes regulated by CPSF6, can fine-tune the antiviral response as well as the responses to other cellular stresses to maintain the tissue homeostasis, which may represent a novel regulatory mechanism for antiviral immunity.